The difference of the salivary volume before and after drinking the rosella tea (Hibiscus sabdariffa) - Islami, Mutiara Indah Permata Sari; Haroen, Edeh Roletta; Tjahajawati, Sri (Universitas Padjadjaran, 2010)
Introduction: Roselle plants (Hibiscus sabdariffa) is one of the herbs that began to be used by the community. Benefits of this plant is quite a lot for health. The portion taken for consumption is the red flower petals. oselle tea is one of the sour beverages which can affect the salivary gland secretion. The purpose of this study is to analyzed the difference of salivary volume before and after drinking roselle tea. Methods: This study has been conducted to 40 students of Faculty of Dentistry, Padjadjaran University, ranging from 18-23 years of age with good general condition. This study is quasi-experimental in vitro study using the paired test analysis with α = 0,05 of the data collected from salivary volume. Results: The result of study indicates that the average of salivary volume before drinking roselle tea is 1,90 milliliter. After drinking roselle tea, the average of salivary volume is 4,54 milliliter. The result of paired test analysis shows that t-test is 16,172 and t-table is 2,022. The value of t-test > t-table. Result of statistic shown there is significant difference of salivary volume before and after drinking roselle tea. Conclusion: There is a difference of salivary volume before and after drinking roselle tea.